Pemberdayaan Ibu Rumah Tangga dalam Upaya Meningkatkan Alternatif Pendapatan Tambahan di PKK Desa Balong Tunjung Gresik: Pengabdian - Siti Asiah Murni; Tumewu, James; Zainuddin, Akhmad; Wahyu Nuraini, Savira; Yeremia Patiung, Marcello (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to improve the entrepreneurial skills of Family Welfare Movement (PKK) women in Balong Tunjung Village through training in the production of alternative recycled-based products, specifically aromatherapy from used cooking oil. Participatory methods were used in the form of practical training, mentoring business groups, and product exhibitions. Results showed significant improvements in processing skills, environmental awareness, and entrepreneurial motivation among participants. This household waste-based innovation has proven to be applicable and has the potential to be developed into a sustainable community-based business unit.